ENGLISH SOCIOLECT INVARIANTS IN MODERN UKRAINIAN SOCIETY - Mischynska, I. (Linguistic and Conceptual Worldviews, 2019)
The article highlights the issue of English social dialect invariants in contemporary Ukrainian society. Language varieties used in society reflect regional, social and ethnic belonging of people who use them. There exists interconnection between a language and society. Nowadays development of democratic values in Ukraine requires to use English as a second oﬃcial language and academic programs in educational establishments are directed to learning English as a main foreign language. Ukrainian society fasces the perspective of implementing English sociolect invariants in various spheres of social life. Peculiarities of a language situation in Ukraine are reflected in the article. A language situation involves the relations that develop between language formations in a society. These formations are determined by many factors, the main of which are diﬀerent social statuses of society members. In modern Ukrainian society there exist a wide range of formations speaking more than one language, therefore the language situation in Ukraine is exoglossic. English terms, professional and sociolect invariants are implemented in various spheres of social life in everyday use of Ukrainian people as a result of growing number of language contacts. In philosophy invariant is determined as ‘an invariable’. Main spheres of English sociolect invariants application are defined in the article. Such types of discourse as media-discourse and business-discourse can be considered the types of dis- course that have acquired the biggest number of terms, professional words and other socially marked words in Ukrainian society. Тhese types of discourse have the strongest impact on social life in a poly- cultural country. Such means of typology research as semantic maps has been used in contemporary linguistics. It is based on the notions that appeared in context of semantic fields research. Semantic fields include words with the common meaning. The methods of semantic field analysis are used in comparative linguistics.The comparative analysis of semantic fields of the business-discourse in the English and Ukrai-nian languages has pointed out to equivalent positions of professional terms and jargon words in these semantic fields. Existence of proper Ukrainian words and notions corresponding to English invariants with the same meaning has proved the universal nature of invariants.
Keywords: sociolect invariants, language situation, business-discourse, language contact, semantic field